ANALISIS KEUNGGULAN KOMPARATIF KOMODITAS KELAPA SAWIT RAKYAT DI KECAMATAN SEKADAU HILIR - SUTARMAN GAFUR, HASWEN SARAGIH, ANI MUANI, (Jurnal Social Economic of Agriculture, 2018)
Comparative Advantage Analysis Commodities Palm Oil In Sekadau (A Case Study of Rural Ensalang Sekadau Hilir Subdistrict)  (Haswen Saragih, under the guidance of Ir. Ani Muani, MS, and DR. Ir. H. Sutarman Gafur, M.Sc)  Regional economic growth is basically influenced by an area of comparative advantage, specialization area,  as well as the economic potential possessed by the area. Therefore, the utilization and development of all the economic potential is a top priority that must be explored and developed in  implementing sustainable local economic development.This study aims to: Analyze the competitiveness of farming folk palm oil (competitive and comparative advantage) and Domestic Resource Cost (BSD) and the Foreign Cost Components. Analyzing the impact of government policies on output and input in oil palm farming. Analyze the competitiveness of the sensitivity to changes in the oil palm farming output and input with the approach in terms of production (GDP per capita). This study used a simple random sampling method the farmer of 50 respondents with purposive.From the analysis of comparative advantage show the coefficient of BSD (Cost Resources Domestic) ˂ 1, which means that the business activity of commodity production of oil palm in the study area has been economically efficient in the utilization of domestic resources, thereby fulfilling the domestic demand is more favorable with increased domestic production. With a coefficient of 0.4 with 95% Confident Interval and standard deviation of 5%, using t  two-tail test directions.Analysis sensitivity palm oil commodity standards conversions factor = 0.73; which means the factors of production BSD ˂ 1; Oil palm business activity economically efficient in the utilization of BSD, so that the activities of oil palm economic activities beneficial to the export activity. The results are expected to sectoral policy makers in agriculture subsectors palm plantations to optimize domestic production factors (BSD) in order to increase the GDP per capita.